Structural and Optoelectronic Properties of CdSe Tetrapod Nanocrystals for Bulk Heterojunction Solar Cell Applications - Nguyen Tam Nguyen Truong; Thao Phuong Ngoc Nguyen; Chinho Park (International Journal of Photoenergy)
Semiconducting CdSe tetrapod nanoparticles were prepared, and their structural and optical properties were examined. The surface capping molecule, octylphosphonic acid, was replaced with butylamine after the particle synthesis. The exchange of surface ligands changed the physical properties of the nanocrystals, which resulted in a slight decrease in the nanoparticles size. The effects of changing surface ligands of CdSe tetrapod nanocrystals on the structural and optoelectronic properties were investigated, and it was found that the surfactant of nanoparticles could affect the device performance by enhancing the charge carrier separation at the active layer interfaces. Power conversion efficiency of the bulk heterojunction solar cells having the structure of glass/ITO/PEDOT:PSS/(CdSe + PCPDTBT)/Al was improved from 1.21% to 1.52% with the use of ligand-exchanged nanoparticles.